PENGARUH PERMAINAN TALI TEMALI TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK HARAPAN BUNDA KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Ningsi, Cici Ayu; Risma, Devi; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the observations that have been conducted by researchers in children aged 5-6 years in TK Harapan Bunda of the Cerenti Districk Kuantan Singingi Regency is still found some problems associated with emotional intelligence. As the most of which seems to be aggressive when playing like the friend's toy, and some of the child tends to anger out on when the mood it can not be met, the child who is like playing alone or over and asked parents to play a game than playing with a friend of his age, children are too difficult to control his feelings (emotion) to share toys with his friend which resulted in the child is poking and prodding his friend, the kid who just shut up when he saw his friend made a mistake while playing with such deliberately pushing his friend to the ground. The study aims to determine the influence of the ropes of emotional intelligence 5-6 yearold children in TK Harapan Bunda of the Cerenti Districk Kuantan Singingi Regency. The research is a research experiment. using one group pretest posttest design. The samples used in this study amounted to 32 children as for the techniques of collecting data used is an observation. The analysis of data by using the program IBM SPSS Statistic The 21. This hypothesis of this study was that there was a significant influence the use of the ropes of emotional intelligence. To determine the hypothesis is accepted or rejected can be seen based on data from IBM SPSS Statistic The 21 can be seen thitung, 39,199 more than ttabel, 2,039 (39,199 > 2,039). Thus Ho was rejected and Ha was received that means there is a significant influence before and after doing an experiment the ropes of emotional intelligence. this can be seen from the influence of the ropes based on calculations using formula Gain of 53, 49 % are in the medium and 46, 51 % affected by other factors.Keywords : Emotional Intelligence, Ropes Game